Knowledge with Flood Disaster Preparedness in Mojokerto District - Windartik, Emyk; Ima Rahmawati (Kirana Publisher (KNPub), 2023)
The high intensity of flooding in Indonesia makes people have to be aware of flood disasters. An important factor in flood disaster management is community preparedness which requires knowledge about flood disaster risks. The purpose of this study was to determine the relationship between the level of knowledge with flood disaster preparedness in the community. This research design is correlation analytic with cross sectional approach. The population of this study were all responsible family heads aged 20-50 years, totalling 143 families. In this study using simple random sampling (n = 38 people). The instrument used was a questionnaire. The results showed that most of the respondents had sufficient knowledge 25 people (65.8%), most of the respondents were alert to flood disasters 25 people (65.8%). The results of the Spearman Rho test analysis obtained a pvalue of 0.000 less than α (0.05) and a coefficient correlation value of 0.678 so that H1 is accepted, which means that there is a strong relationship between the level of knowledge and preparedness for flood disasters in the community. Knowledge will affect the community's concern to be ready and alert in anticipating disasters, especially for those who live in areas vulnerable to flooding.